Síndrome de Burnout em cirurgiões-dentistas com diferentes atuações profissionais - Zucolotto, Miriane [UNESP]; Jordani, Paula Cristina [UNESP]; Bonafé, Fernanda [UNESP]; Garcia, Patrícia Petromilli Nordi Sasso [UNESP]; Maroco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (Leibniz Institute for Psychology (ZPID), 2014)
Objective: To compare the mean scores of the three dimensions of Burnout (Exhaustion, Disengagement/cynicism and Professional efficacy) in dentists with different professional occupations. Method: The sample was composed by 284 undergraduate dental students, 70 dentistry faculty and 60 dentists working in the public health service. The Maslach Burnout Inventory (MBI) was used. Psychometric characteristics of the MBI in the different samples were tested. Mean scores were compared using Multivariate Analysis of Variance (MANOVA). Results: The MBI showed adequate reliability and validity in different samples. The students had a significantly higher mean score on exhaustion than the faculty and the dentists of the public service (p < 0.001). Faculty presented the lowest levels of disengagement/cynicism (p < 0.001). The professional efficacy of students was significantly lower than that of the faculty (p < 0.001). Conclusion: There are differences in the incidence of the Burnout Syndrome amongst students and dentistry professionals. This should be considered for future studies aiming to minimize the effects of the syndrome in dentists.

Objetivo: Comparar os valores médios de Exaustão, Descrença e Eficácia/Realização Profissional em profissionais da Odontologia com diferentes atuações profissionais. Método: A amostra foi constituída por 284 estudantes e 70 professores de graduação em Odontologia e 60 cirurgiões-dentistas atuantes no serviço público de saúde. Utilizou-se o Inventário de Burnout de Maslach (MBI). As características psicométricas do MBI nas diferentes amostras foram testadas. Os valores médios foram comparados por meio de Análise de Variância Multivariada (MANOVA). Resultados: O MBI apresentou adequada confiabilidade e validade nas diferentes amostras. Os estudantes apresentaram valores médios de Exaustão significativamente maiores que os professores e os dentistas do Serviço Público (p < 0,001). A Descrença foi significativamente menor entre os docentes (p < 0,001). A Eficácia/Realização Profissional dos estudantes foi significativamente menor do que a dos professores (p < 0,001). Conclusão: Existem diferenças entre os profissionais da Odontologia quanto à Síndrome de Burnout, o que deve ser considerado para a realização de futuros estudos visando minimizar os efeitos da síndrome nos cirurgiões-dentistas.
Burnout syndrome in dentists with different professional occupations
Keywords: Burnout professional; Dentistry; Occupational health; Public health; Students; Faculty; Esgotamento profissional; Odontologia; Saúde ocupacional; Saúde pública; Estudantes; Docentes